SUCCESSFUL TREATMENT FOR ATYPICAL HEMOLYTIC UREMIC SYNDROME IN A PUERPERA - O. N. Ulitkina; Zh. S. Filippovskaya; E. I. Prokopenko; A. M. Ovezov; V. V. Likhvantsev (Общая реаниматология, 2016)
Objective: to show the problems of differential diagnosis and treatment of atypical hemolytic-uremic syndrome in a 23-year-old patient.Results. Eculizumab (Soliris), (Alexon Pharmaceuticals Inc., USA) that is a glycosylated humanized monoclonal antibody to immunoglobulins (IgG2/4k) is shown to be effective in treating this disease.Conclusion. Atypical hemolytical-uremic syndrome in pregnancy is a disease, whose treatment difficulties are largely associated with the problem of differential diagnosis with thrombotic thrombocytopenic purpura and man-ifestations of multiple organ dysfunction. The treatment for this disease gives a key role to Eculizumab.